PENGARUH TUNJANGAN PERBAIKAN PENGHASILAN (TPP) DAN SISTEM PENILAIAN E-KINERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PPK SUNGAI DAN PANTAI II SNVT PJSA BBWS BRANTAS KEDIRI - Ahmad Syaifudin Zuhri; Arisyahidin Arisyahidin; Ahsin Daroini (Commodities, Journal of Economic and Business, 2021)
Minister of Home Affairs Regulation Number 59 of 2007 concerning Regional Financial Management, states that local governments can provide additional income to civil servants based on objective considerations regarding to financial capacity. The implementation of employee performance appraisals which is done by each work unit, in this case the application of the assessment is done using a system called e-performance. The purpose of this study was (1) to examine the significance of the effect of income improvement support and the e-performance appraisal system on employee performance. (2) Testing the significance of the income improvement support (TPP) on employee performance. (3) Examining the effect of the e-performance appraisal system on employee performance. This type of research is quantitative research using multiple linear regression and hypothesis testing using f test, t test and the coefficient of determination. This research was conducted at the PPK Sungai and Pantai II Office of SNVT PJSA BBWS Brantas Kediri with a sample of 55 ASN employees. The results of this study are (1) the income improvement support (TPP) and the e-performance appraisal system has positive and significant effect on employee performance (2) the income improvement support (TPP) have a positive and significant effect on employee performance (3) the e-performance appraisal system has positive and significant effect on employee performance.